Outbreak report of SARS-CoV-2 infection by airborne transmission: Epidemiologic and molecular evidence - María-Cristina Navas; Juan D. Cerón; Wbeimar Aguilar-Jiménez; María T. Rugeles; Francisco J. Díaz (Biomédica: revista del Instituto Nacional de Salud, 2023)
Introduction: It has been shown that the transmission of SARS-CoV-2 occurs mainly by air, and the risk of infection is greater in closed spaces. Objective: To describe the epidemiology, virology and molecular characterization of a COVID-19 outbreak at a closed vaccination point during the third wave of SARS-CoV-2 in Colombia. Materials and methods: Diagnostic tests, interviews, sampling, cell cultures and viral sequencing were carried out, the latter being molecular characterization and lineage identification. Results: Seven workers were positive for SARS-CoV-2; among these, 3 samples were analyzed, plus an additional sample belonging to the mother of the presumed index case; all samples were identified with lineage B.1.625, with a maximum of 2 nucleotides difference between them. Conclusions: Variant B.1.625 was identified as the cause of the COVID-19 outbreak, and a co-worker was also identified as the index case. Unexpectedly, attending a vaccination day became a risk factor for acquiring the infection.